Incidence of temporomandibular joint clicking in adolescents with and without unilateral posterior cross‐bite: a 10‐year follow‐up study. (6th August 2015) - Michelotti, A.; Iodice, G.; Piergentili, M.; Farella, M.; Martina, R.
Summary: Among different malocclusions, posterior cross‐bite is thought to have a strong impact on the correct functioning of the masticatory system. The association between unilateral posterior cross‐bite (UPCB) and temporomandibular joint (TMJ) clicking, however, remains still controversial. The aim of this study was to investigate whether the presence of UCPB during early adolescence increases the risk of reporting TMJ clicking after a long‐term follow‐up. A longitudinal survey design was carried out in a group of 12‐year‐old young adolescents, who were examined at baseline for TMJ clicking sounds and unilateral posterior cross‐bite. After 10 years, 519 subjects could be reached by a telephone survey. Standardised questions were used to collect self‐reported TMJ sounds and to determine whether participants had received an orthodontic treatment. Logistic regression analysis revealed a significant association between unilateral posterior cross‐bite and subjectively reported TMJ clicking (odds ratio = 6·0; 95% confidence limits = 3·4–10·8; P < 0·0001). The incidence of TMJ clicking was 12%. At a ten‐year follow‐up, self‐reports of TMJ clicking were significantly associated with the presence of UPCB at baseline, but not with the report of having received an orthodontic treatment. Within the limitation of this study, the presence of unilateral posterior cross‐bite in young adolescents may increase the risk of reporting TMJ sounds at a 10‐year follow‐up. The provision of an orthodontic treatment, however, does not appear to reduce the risk of reporting TMJ sounds.